Morpho-physiological analysis of adaptive responses of common bean (Phaseolus vulgaris L.) to drought stress. Thesis (Ph.D.) - Polanía Perdomo, José A. (Universitat Autònoma de Barcelona. Departament de Biologia Animal, Biologia Vegetal i Ecologia Unitat Fisiologia Vegetal, 2016)
Common bean (Phaseolus vulgaris L.) is the most important food legume in the diet of poor people in the tropics. This legume is cultivated by small farmers and is usually exposed to unfavorable conditions with minimum use of inputs. Drought and low soil fertility, especially phosphorus (P) and nitrogen (N) deficiencies, are major limitations to bean yield in smallholder systems. Beans can derive part of their required N from the atmosphere through symbiotic nitrogen fixation (SNF). Drought stress severely limits SNF ability of plants. Identification of traits associated with drought resistance contributes to improving the process of designing bean genotypes adapted to these conditions.